Sustainable development, water resources management and women's empowerment: The Wanaraniya water project in Sri Lanka - Aladuwaka S.; Momsen J. (Gender and Development, 2010)
Water is one of the most important natural resources, and its effective management is essential given its scarcity. In rural Sri Lanka, the management of available water resources needs special attention because investment for water resource improvement is hard to obtain, and water itself is relatively scarce in the drier areas of the country. The Wanaraniya Water Project pipes water 6.5km from its source to individual houses in the village, saving women daily time and effort. The project is founded on commitments to community participation and the adoption of local knowledge. It was initiated by women, and has been operated and managed by them for the last six years. This study argues that the project can serve as a model for better planning of water management, and focuses on the unique strategies and innovative methods that have been used. In particular, it shows the impact of involvement in the project on women’s empowerment. The implementation of the project has helped women to improve their leadership qualities, confidence, self-reliance, and gain more power in the community through their successful establishment of a village water supply.
Keywords: approches et analyses; asie; cours; discipline; développement; développement participatif; environnement; géographie; histoire et politique; justice sociale; pol4022; premier cycle; ressource en ligne; régions géographiques; sciences humaines; sri lanka; thématiques; études de genres

Transnational migration theory in population geography: gendered practices in networks linking Canada and India - Walton-Roberts, Margaret (Population, Space and Place, 2004)
Geographers have recently suggested that transnational migration theory can contribute to the development of a critical population geography. What might such a critical population geography look like? In this paper I explore this in three ways. Firstly I offer some comments on why geographers have been slow to adopt a transnational focus on migration, and secondly I examine how gender has been underplayed in transnational literature. Thirdly I draw upon some examples from research on transnational immigrant networks between Canada and India. I focus on the specifics of Punjabi marriage migration networks to demonstrate how the practice of spousal selection has become globalised for certain diasporic communities. These examples offer a preliminary illustration of what a critical population geography, attuned to issues of gendered transnational processes, might contribute to current debates. Copyright © 2004 John Wiley & Sons, Ltd.
Keywords: amériques; approches et analyses; asie; canada; cours; discipline; géographie; histoire et politique; inde; mariage; mariages transnationaux; migration; premier cycle; punjab; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sex2283; thématiques